Tumor-like Lesions of Bone and Soft Tissues and Imaging Tips for Differential Diagnosis - Örgüç, Sebnem; Arkun, Remide (Seminars in Musculoskeletal Radiology, 2020)
In the musculoskeletal system, tumor-like lesions may present similar imaging findings as bone and soft tissue tumors and can be defined as tumors on radiologic examinations. Misinterpretation of the imaging findings can lead to inappropriate clinical management of the patient.There is still some debate regarding the pathophysiology and origin of tumor-like lesions that include congenital, developmental, inflammatory, infectious, metabolic, reactive, posttraumatic, post-therapeutic changes, and some miscellaneous entities causing structural changes. Although tumor-like lesions are historically defined as non-neoplastic lesions, some of them are classified as real neoplasms.We discuss a spectrum of entities mimicking tumors of bone and soft tissues that include various non-neoplastic diseases and anatomical variants based on imaging findings.
Keywords: tumor-like lesions; bone; soft tissues